An ultra-sensitive and easy-to-use assay for sensing human UGT1A1 activities in biological systems - Ya-Di Zhu; Hui-Lin Pang; Qi-Hang Zhou; Zi-Fei Qin; Qiang Jin; Moshe Finel; Yi-Nan Wang; Wei-Wei Qin; Yin Lu; Dan-Dan Wang; Guang-Bo Ge (Elsevier, 2020)
The human UDP-glucuronosyltransferase 1A1 (UGT1A1), one of the most essential conjugative enzymes, is responsible for the metabolism and detoxification of bilirubin and other endogenous substances, as well as many different xenobiotic compounds. Deciphering UGT1A1 relevance to human diseases and characterizing the effects of small molecules on the activities of UGT1A1 requires reliable tools for probing the function of this key enzyme in complex biological matrices. Herein, an easy-to-use assay for highly-selective and sensitive monitoring of UGT1A1 activities in various biological matrices, using liquid chromatography with fluorescence detection (LC-FD), has been developed and validated. The newly developed LC-FD based assay has been confirmed in terms of sensitivity, specificity, precision, quantitative linear range and stability. One of its main advantages is lowering the limits of detection and quantification by about 100-fold in comparison to the previous assay that used the same probe substrate, enabling reliable quantification of lower amounts of active enzyme than any other method. The precision test demonstrated that both intra- and inter-day variations for this assay were less than 5.5%. Furthermore, the newly developed assay has also been successfully used to screen and characterize the regulatory effects of small molecules on the expression level of UGT1A1 in living cells. Overall, an easy-to-use LC-FD based assay has been developed for ultra-sensitive UGT1A1 activities measurements in various biological systems, providing an inexpensive and practical approach for exploring the role of UGT1A1 in human diseases, interactions with xenobiotics, and characterization modulatory effects of small molecules on this conjugative enzyme.